CONTRASTIVE METHOD: USING THE NATIVE LANGUAGE AS A SCAFFOLD RATHER THAN AN INTERFERENCE - Айнур Сейитбердыева (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
The article examines the didactic status of the native language (L1) in the process of teaching a foreign language (L2). The author analyzes the historical evolution of the contrastive method: from Robert Lado’s "strong" hypothesis to Larry Selinker’s interlanguage theory. The paper substantiates the transition from combating interference to utilizing cross-linguistic parallels as a tool for developing students' cognitive reflection. The concept of a "balanced bilingual approach" is proposed, where an error is viewed not as a defect, but as a systemic stage in the formation of communicative competence.